L’univers sonore de Sredni Vashtar (Andrew Birkin, 1981) - Sophie Mantrant (Cahiers Victoriens et Edouardiens)
In 1981, Andrew Birkin was awarded the BAFTA for Best Short Film for his adaptation of Saki’s ‘Sredni Vashtar’ (1911). This article explores the film’s soundscape to show how it participates in the construction of the oppositional system that underpins Saki’s short story. Carl Orff’s ‘O Fortuna’ is used as a symbolic signifier strictly associated with the world of the child, as opposed to the adult’s. The piece interacts with diegetic sounds to create a complex web of echoes and dissonances. Thus, ‘O Fortuna’ is set in sharp contrast with the tick-tock of the clock that can be heard in the dreary Edwardian house. As it is associated with the colour red, the music also highlights by contrast the greyness of a constraining adult world. Colour and music thus combine to give shape to the world of a child chafing under the yoke of the real.